Determination of the pH and count of mesophilos in black prochilodus meat (Prochilodus nigricans) from the markets of the city of Pucallpa, Ucayali - Ponce P., Nathaly (2021)
The aim of this study was to determine the pH and the count of mesophiles in black prochilodus (“boquichico”) meat (Prochidolus nigricans), from the markets of the city of Pucallpa, Ucayali. In total, 115 samples of boquichico specimens were collected from the 23 stalls distributed in the 5 markets of the city (5 samples per stall, considering the stall as a lot), through a non-probabilistic convenience sampling. The processing was carried out by measuring the pH of the meat and the analysis for the count of mesophiles with the SPC method (aerobic plate count). The averages of the pH values in boquichico meat by market were below the neutral value (pH=7.0), but were higher in the samples from markets 3 and 5; likewise, the mesophilic counts in meat exceeded the Maximum Allowable Limits in 4 of the 23 stalls (two from market N° 1, one from market N° 2 and one from market N° 3). It is concluded that the boquichico meat commercialized in the markets of the city of Pucallpa is not suitable for consumption in three stalls in two Callería markets and in one stall in a market in Manantay.